Interaction of CCND2, CDKN1A, and POLD3 Variants in Mexican Patients with Colorectal Cancer - Alvizo-Rodríguez, Carlos Rogelio; Ayala-Madrigal, María de la Luz; Flores-López, Beatriz Armida; Partida-Pérez, Miriam; Macías-Gómez, Nelly Margarita; Peregrina-Sandoval, Jorge; Suárez-Villanueva, Alexis Sayuri; Moreno-Ortiz, José Miguel; Cervantes-Ortiz, Sergio; Maciel-Gutiérrez, Víctor Manuel; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Colorectal cancer is the second cause of death by cancer around the world. Sporadic colorectal cancer is the most frequent (75%), and it is produced by the interaction of environmental, epigenetic, and genetic factors. The accumulation of single-nucleotide variants in genes associated with cell proliferation, DNA repair, and/or apoptosis could confer a risk to cancer. The aim of this study was to analyze the gene–gene interactions among CCND2 (rs3217901), CDKN1A (rs1059234 and rs1801270), and POLD3 (rs3824999) vari- ants in Mexican patients with colorectal cancer. Methods: We collected peripheral blood samples from 185 patients with sporadic colorectal cancer before treatment and from 185 unre- lated blood donors as the reference group; all participants signed an informed consent form. DNA extraction was performed by Miller and Cetyltrimethylammonium bromide (CTAB)/ Dodecyltrimethylammonium bromide (DTAB) methods. Polymerase chain reaction– restriction fragment length polymorphism followed by polyacrylamide gel electrophoresis stained with AgNO3 methods were used to identify the variants rs3217901, rs1059234, rs1801270, and rs3824999. Odds ratio and single-nucleotide variant interaction were determined by single-locus analysis and Multifactorial Dimensionality Reduction software, respectively. Results: No association was found for CCND2 and CDKN1A variants; yet, a significant association for the GG genotype, G allele, and recessive and additive models for the POLD3 variant was observed (P < .05). The single-nucleotide variant–single-nucleotide vari- ant interaction revealed the combination rs1059234, rs3217901, and rs3824999 as the best model and the comparison showed an increased risk (P < .05). Conclusion: Single-locus and gene–gene interaction analyses disclosed that both the rs3824999 (POLD3) variant and the combination of rs3217901 (CCND2), rs1059234 (CDKN1A), and rs3824999 (POLD3) genotypes increase the risk for colorectal cancer in Mexican population.